Evaluation of Disaster Course Learning Methods in the Academic Phase of Medical Education Study Program - Ahmad Muttaqin Alim; Nurul Qomariyah; Afifah Khoiru Nisa (Universitas Ahmad Dahlan, 2021)
This study was designed to evaluate students and lecturer perceptions of the learning methods used in Disaster Course. A qualitative cross-sectional descriptive study with focus group discussion (FGD) was conducted. Twenty students and eight Disaster’s lecturers in Faculty of Medicine Universitas Ahmad Dahlan participated in the study. The results showed that students have different perceptions from lectures. Students assessed the learning methods used are less effective due to their role as a passive learner. While the lectures assessed the effectiveness of their teaching methods varied according their ability to teach in large classes.